2021
DOI: 10.1002/pon.5748
|View full text |Cite
|
Sign up to set email alerts
|

The role of interpretation biases and symptom burden in fear of cancer recurrence/progression among ovarian cancer survivors

Abstract: Background Models of fear of cancer recurrence or progression (FCR/P) suggest that the way in which people interpret ambiguous physical symptoms is an important contributor to the development and maintenance of FCR/P, but research has not investigated this claim. The aim of this study is to fill that gap. Methods This was a cross‐sectional study. Sixty‐two women with ovarian cancer reported completed measures of FCR/P, an interpretation bias task and a symptom checklist. The healthy control group (n = 96) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 39 publications
(55 reference statements)
3
21
1
1
Order By: Relevance
“…Among those with the lowest levels of interpretation bias, pain and FCR were not significantly related. These results were predicted, but not consistent with our earlier study with ovarian cancer survivors where we failed to find the predicted moderation effect (Pradhan, Sharpe, Butow, & Russell, 2021). There are a number of possible reasons why the model might have been better supported in a breast cancer sample than an ovarian cancer sample.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Among those with the lowest levels of interpretation bias, pain and FCR were not significantly related. These results were predicted, but not consistent with our earlier study with ovarian cancer survivors where we failed to find the predicted moderation effect (Pradhan, Sharpe, Butow, & Russell, 2021). There are a number of possible reasons why the model might have been better supported in a breast cancer sample than an ovarian cancer sample.…”
Section: Discussioncontrasting
confidence: 99%
“…The responses were then categorized into threat/health-related (1) (e.g., injection) or neutral (0) (e.g., sewing). This task has previously been used in relation to cancer and FCR/P (Pradhan, Sharpe, Butow, & Russell, 2021).…”
Section: Interpretation Bias (Ib)mentioning
confidence: 99%
See 2 more Smart Citations
“…The current study examined whether interpretation bias is associated with FCR, as prior research has suggested ( Lee-Jones et al, 1997 ; Lichtenthal et al, 2017 ; Pradhan et al, 2021 ). We also examined somatic, demographic and medical correlates of cancer-related interpretation bias.…”
Section: Discussionmentioning
confidence: 99%